Doing Open Science in a Research-Based Seminar: Students’ Positioning Towards Openness in Higher Education - Truan, Naomi; Dressel, Dennis (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
This study investigates undergraduate students’ attitudes towards and experiences with open education practices (OEP) in a research-based linguistics seminar. Data was collected through written assignments in which two groups of students in subsequent terms were surveyed on their willingness to publish (a) academic posters in open access (OA); (b) teaching concepts as open educational resources (OER); and (c) personal reflections on the research process in OA. Through qualitative data analysis, we examine students’ apprehensions and motivations to publish their artifacts. We find that key motivators are a sense of belonging, personal reward, and an active contribution to a culture of collaboration, whereas apprehensions are grounded in concerns about the quality of their work, uncertainties about licensing, and fear of vulnerability through visibility. We show that open science practices and OEP can be combined synergistically in process-oriented, research-based, and collaborative seminar concepts, and we formulate recommendations for lecturers on how to successfully address OEP in the classroom.